Computational fluid mixing - Chris Rielly; Jolius Gimbun (2009)
Computational fluid dynamics (CFD) is an extremely powerful tool for solving problems associated with flow, mixing, heat and mass transfer and chemical reaction. Although the equations of motion for fluid flow were established in the first half of the nineteenth century (e.g. Navier, 1822; Stokes, 1845), it was not until the arrival of digital computers in the 1960s and 1970s that it became feasible to perform numerical simulations of complex engineering flows. In these early days, CFD was a very much a research tool and most of the early work was aimed at developing numerical methods, solution algorithms and Reynolds-averaged turbulence models. However, in the 1980s, the first commercial codes emerged — e.g. PHOENICS, FLUENT, FIDAP, Star-CD, FLOW3D (which later became CFX) — providing general purpose software packages for both academic and industry users. The aerospace and automotive industries were amongst the first to embrace the use of CFD in engineering design, but from the 1990s onwards commercial codes have found widespread applications, for example in: biomedical engineering, environmental and atmospheric modelling, meteorology, chemical reaction engineering and more recently in the food and beverage industries. This chapter will focus on mixing vessel applications for the last two of these industry sectors, where CFD is increasingly used to provide process understanding and semi-quantitative analysis. In their review, Norton and Sun (2006) presented a graph showing the very significant increase in the number of peer-reviewed papers related to CFD applications to food process engineering. Figure 0.1 is an updated version of this graph, containing more recent data and showing that the number of papers that specifically analyse food mixing operations using CFD is still relatively small. In contrast, there are a vast numbers of papers on CFD simulation of (i) other food process operations, (e.g. drying, sterilisation, thermal treatment and extrusion, many of which are described by Sun (2007)) and (ii) more conventional mixing operations in the chemicals and specialty product industries (see for example, Marshall and Bakker (2004)). This chapter will outline the background knowledge required for CFD studies, present some examples of CFD modelling of mixing vessel flows and finally will discuss the current difficulties in applying this approach to food mixing processes.